Trends of HIV-1 and HIV-2 prevalence among pregnant women in Guinea-Bissau, West Africa: possible effect of the civil war 1998–1999. Issue 6 (4th July 2007) - Månsson, Fredrik; Alves, Alfredo; Silva, Zacarias José da; Dias, Francisco; Andersson, Sören; Biberfeld, Gunnel; Fenyö, Eva Maria; Norrgren, Hans
Abstract : Objectives: Sentinel surveys in Bissau, the capital of Guinea-Bissau, have shown low prevalence of HIV-1 but high HIV-2 prevalence before 1998. Guinea-Bissau experienced a civil war in 1998–1999. To examine specifically the trends of HIV prevalence from antenatal surveys in Bissau, Guinea-Bissau in 1987–2004, and whether the civil war in 1998–1999 could have an effect on HIV prevalence levels after the conflict. Methods: Since 1987, anonymous HIV testing in delivering women has been performed at the maternity clinic, Simão Mendes National Hospital, Bissau, as part of the national sentinel surveillance programme. Consecutive sampling was performed for approximately 3 months between September and December each year. Serological analyses were performed at the National Public Health Laboratory in Guinea-Bissau. Results: A total of 20 422 women were tested for HIV between 1987 and 2004. The total HIV-1 prevalence increased from 0.0% in 1987 to 4.8% in 2004 and the total HIV-2 prevalence decreased from 8.3% in 1987 to 2.5% in 2004. The HIV-1 prevalence increased from 2.5% in 1997 to 5.2% in 1999, but stabilized in subsequent years. Conclusions: There was a significant increase in HIV-1 prevalence in the years 1987–2004 and a significant decline in HIV-2 prevalence over the same period. The civil war in 1998–1999 may have sparked HIV-1 transmission, as HIV-1 prevalence more than doubled between 1997 and 1999, but there is no evidence of a long-term effect on the trends of HIV-1 or HIV-2 prevalence.